Usage of Financial Technology: A Study on Lhokseumawe Community Based on UTAUT Model - Afrah, Zahriatul; Mahmud, Taufiq; Rahmawati; Taj, Sahrish (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2025)
In today's digital age, every social activity involves the use of technology. Almost every industry, including finance, benefits from technological advances for innovation. Financial technology is an example of innovation in the financial industry and can be seen in the form of payments, electronic aggregators, risk and investment management, peer-to-peer lending, etc.The purpose of this study was to determine the effect of performance expectations, expected effort, social influence and facilitating conditions on the use of financial technology in the community in Lhokseumawe City. This research uses quantitative methods and uses non-purposive sampling techniques. The technique used in this research uses non-purposive sampling. Probability sampling technique is a sampling technique that provides equal opportunities for each member of the population to be selected as a sample. The population used is the general public of lhokseumawe city with a sample size of 100 respondents through distributing questionnaires. The results of this study indicate that partially the Performance expectancy and Effort Expectancy variables have a positive effect on utilization